Analysis of the effects of Beta-Amyloid and age on cell signalling in rat hippocampus : effect of treatment with polyunsaturated fatty acids - Minogue, Aedín (Trinity College (Dublin, Ireland). Department of Microbiology, 2005)
Long-term potentiation (LTP) is considered to be a possible neurophysiological model for learning and memory and consistent with this, is the observation that LTP is sensitive to stress, injury and insult. This thesis investigates the effects of amyloid- β (Aβ) and subsequent cellular signalling pathways on expression of LTP in perforant-path granule cell synapses. Evidence suggests that an age-related impairment in LTP exists in hippocampus and that upregulation of proinflammatory signalling may underpin this effect. This observation indicates that hippocampus may be more susceptible to stress or insult with age. Consequently, the effects of Aβ administration on LTP in hippocampus of adult and aged rats was investigated.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin